AN ANALYSIS OF THE PROCESS OF ACCELERATION OF SEISMIC ENERGY EMISSION IN LABORATORY EXPERIMENTS ON DESTRUCTION OF ROCKS AND BEFORE STRONG EARTHQUAKES ON KAMCHATKA AND IN ITALY - Di Giovambattista R.; Tyupkin Yu.S. (My University, 2001)
The time-to-failure model is a technique in which a failure function is fitted to a time series of accumulated Benioff strain before a large earthquake. We analyze the relation of the time-to-failure model to the hypothesis of fractal structure of seismicity. A power law failure function (Varnes, 1989; Bufe and Varnes, 1993) and its log-periodic generalization Sornette and Sammis, 1995 are discussed. The results of application of the log-periodic time-to-failure model to the analysis of the process of acceleration of seismic energy emission in the laboratory experiments on rock destruction and before strong earthquakes on Kamchatka and in Italy are presented.
Keywords: Earthquakes; Time-to-failure model